2017
DOI: 10.1080/22797254.2017.1413955
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring dynamics and driving forces of lake changes in different seasons in Xinjiang using multi-source remote sensing

Abstract: Lakes are important for ensuring the development of the regional economy and ecological security. Based on MODIS and Landsat TM/OLI remote sensing images captured in 2005-2015 and a Combined Water Index (CWI), this paper extracted information on changes in the temporal and spatial characteristics and driving forces for lake areas in Xinjiang during past 11 years in different seasons (April, July and September). The results showed that over this time period, the area of the lakes exhibited an increasing trend. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
2
10
1
Order By: Relevance
“…Lake ice was identified as part of lake area for April in this paper, the present study noted that lakes area were larger than that reported in the existing literature due to different reflectivity for ice and water 2,17 . There may be also some uncertainty with large water bodies, as the spatial resolution of MODIS is 500 m each day, which is relatively low.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Lake ice was identified as part of lake area for April in this paper, the present study noted that lakes area were larger than that reported in the existing literature due to different reflectivity for ice and water 2,17 . There may be also some uncertainty with large water bodies, as the spatial resolution of MODIS is 500 m each day, which is relatively low.…”
Section: Discussioncontrasting
confidence: 42%
“…The seasonal variation trend was similar as lake area obtained by Jing et al . 17 , such as Ebi Lake, Ulungu Lake and Ayakkum Lake. Bai et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lakes are important reservoirs of water resources in arid areas and an important part of the water cycle in arid areas (Song et al, 2013;Song et al, 2013;Kaplan and Avdan, 2017). They are among the most sensitive geographical units in response to global climate change and are also affected by human activities (Jing et al, 2018). In recent decades, inland lakes have undergone drastic changes due to natural environmental changes and human activities (Feng et al, 2016;Deng and Chen, 2017;Deng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are still few detailed analyses of changes in different lakes and the quantitative impact of local climate and human activities (Yu et al, 2020). The lakes in Xinjiang show different change trends at different altitudes (Jing et al, 2018); with the influence of complex topographic and geomorphic conditions, the types of lakes in the region are diverse. Lakes are distributed in different geomorphic types such as plains (altitude <1,500 m), mountains (1,500 m <altitude <3,500 m), and plateaus (altitude >3,500 m).…”
Section: Introductionmentioning
confidence: 99%